2016
DOI: 10.1051/0004-6361/201628297
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of an exceptionally bright giant arc atz= 2.369, gravitationally lensed by thePlanckcluster PSZ1 G311.65−18.48

Abstract: As part of an all-sky follow-up of the Planck catalogue of Sunyaev-Zeldovich (SZ) cluster candidates detected in the first 14 months of data, we are observing cluster candidates in the southern sky in the optical imaging and spectroscopy through an ESO Large Programme. Inspection of ESO New Technology Telescope (NTT) R-and z-band imaging data from our programme has revealed an unusually large and bright arc in the field of PSZ1 G311.65−18.48. We establish the basic photometric and morphological properties of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
55
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(62 citation statements)
references
References 31 publications
(26 reference statements)
7
55
0
Order By: Relevance
“…We find that it contains strong evidence for direct escape of Lyman α photons through a perforated optically thick medium. The galaxy was serendipitously discovered in follow-up imaging of its lensing cluster, which was discovered through its Sunyaev-Zel'dovich effect in the Planck data (Planck Collaboration XXIX 2014) and was first reported and described by Dahle et al (2016). This is to our knowledge the first unambiguous detection of this type of spectral signature, and it bears remarkable resemblance to theoretical predictions of, for instance, Behrens et al (2014).…”
Section: Introductionmentioning
confidence: 68%
“…We find that it contains strong evidence for direct escape of Lyman α photons through a perforated optically thick medium. The galaxy was serendipitously discovered in follow-up imaging of its lensing cluster, which was discovered through its Sunyaev-Zel'dovich effect in the Planck data (Planck Collaboration XXIX 2014) and was first reported and described by Dahle et al (2016). This is to our knowledge the first unambiguous detection of this type of spectral signature, and it bears remarkable resemblance to theoretical predictions of, for instance, Behrens et al (2014).…”
Section: Introductionmentioning
confidence: 68%
“…The galaxy is designated PSZ1-ARC G311.6602-18.4624 as in the discovery paper (19). The arc segments referred to in the discovery paper (19) as S1, S2 and S3 are here referred to as Arc 1, Arc 2 and Arc 3, respectively. The counterarc was not yet confirmed as part of the lensed system in the discovery paper.…”
Section: Conventionsmentioning
confidence: 99%
“…The Lyman-α profile indicated that it was a prime candidate for strong LyC escape through a narrow channel oriented towards Earth (13). Such a LyC channel should appear as a multiply-imaged, compact source coincident with some of the brightest regions seen in the extended, non-ionizing stellar continuum (19) when observed using telescopes with sufficient resolution and ultraviolet capabilities.…”
mentioning
confidence: 99%
“…In the optical, it is one of the brightest gravitationally lensed high-z star-forming galaxies known so far (e.g., Yee et al 1996;Allam et al 2007;Belokurov et al 2007;Smail et al 2007;Lin et al 2009;Wuyts et al 2010;Bayliss et al 2011;Dahle et al 2016;Marques-Chaves et al 2017), with an apparent total magnitude of R=19.73±0.01. Even after accounting for the magnification produced by the lensing group of galaxies (μ HST =8.5±0.5), it is still very luminous in the rest-frame UV with an absolute magnitude M UV =−23.4, two-and-a-half magnitudes more luminous than typical LBGs (L UV * ) at a similar redshift (Reddy & Steidel 2009).…”
Section: Physical Propertiesmentioning
confidence: 99%